DETERMINAN FAKTOR-FAKTOR YANG MEMPENGARUHI BESARAN IMBAL JASA AUDITOR EKSTERNAL - Arum Ardianingsih; Juandy Seiver Langelo (Fakultas Ekonomi Universitas Pekalongan, 2022)
Audit is an activity of monitoring and evaluating the effectiveness of internal control and the fairness of the financial statements. The purpose of the audit is to add value to the company`s operations and improve the reliability of financial reporting. Large company tend to have complex transactions, business divisions, many subsidiaries and large assets. As a result, the audit completion takes longer and the amount of external auditor fees increases. Companies sometimes also have political interests to gain access to credit facilities and make the company more risk, as a result, the audit fees will be higher. This study examine the effect of political connections, business complexity and firm size on the amount of external auditor fees. The purpose of the study was to obtain empirical evidence abaut the effect of political connections, business complexity and firm size on the amount of external fees. The research data was taken using purposive sampling technique. The analysis technique uses classical assumption test, multiple linear regression and hypothesis testing. The results of the study show that political connections have a significant negative effect on the amount of fees for external auditors, while business complexity and company size have a significant positive effect on the amount of fees for external auditors